Analisis Pelaksanaan Program Kemitraan Terhadap Perkembangan UKM Binaan PTPN III Medan - Nindita Prajwalita; Hasan Basri Tarmizi (Ekonomi dan Keuangan, 2015)
Analysis of the execution of the UKM Development Partnership Program Against Patronage PTPN III Medan" the purpose of this study was to: To investigate the implementation of the partnership program PTPN III Medan in lending to UKM, Analyze the effect of the implementation of the partnership program for UKM income trained partners PTPN III Medan, Analyze the effect of the implementation of the partnership program on employment by the partners UKM PTPN III Medan.in data collection, the author uses secondary data coming from PTPN III Medan, also uses the population and the sample coming from the SME trained partners PTPN III Medan as many as 29 samples.Writer analyze and evaluate which results in that there are differences in income and employment before and after becoming trained partners PTPN III Medan is an increase of the income and employment of the UKM.Keywords : Implementation of UKM development program